Determinants of continuous usage intention of e-hailing apps: A study on Gen Z users - Ab. Aziz, Nasuhar; Ong, Mohd Hanafi Azman; Mazlan, Nur Alia Maisarah; A. Malek @ Abdul Malek, Syazwani; Mohd Shafie, Siti Nurhafizah; Nafi, Mohd Noor Azam; Amran, Azzah; Baistaman, Julaina (International Journal of Accounting, Finance and Business, 2026)
E-hailing applications (EHAs) have revolutionized urban mobility, yet limited research has examined the determinants of their continued use among Gen Z. This study explores the influence of expectation, economic value, and online review on Gen Z continuous intention to use EHAs, with satisfaction evaluated as a mediating variable. A cross-sectional survey was administered to 272 undergraduate’s students at Universiti Teknologi MARA (UiTM) Kota Bharu. Data were analyzed using Structural Equation Modelling. Descriptive statistics were employed to profile the sample. Results reveal that all proposed factors significantly influence continuous usage intention, with satisfaction mediating these effects. The findings provide theoretical insights into post-adoption behaviour in digital transportation services and offer practical recommendations for e-hailing providers to enhance user satisfaction and long-term engagement.